Relevance of Earnings Value, Book Value, and Operating Cash Flow in Manufacturing Companies in Indonesia - Dwi Fitri Puspa; Ietje Nazaruddin; Resti Yulistia M; Arie Frinola Minovia (Universitas Muhammadiyah Yogyakarta, Indonesia, 2023)
Research aims: This study examines the value relevance of accounting information consisting of earnings information, book values, and operating cash flows after Indonesia uses the full convergence of IFRS Financial Accounting Standards.Design/Methodology/Approach: The value relevance test was conducted using Ohlson's (1995) pricing model and Easton and Harris' (1991) return model. The valuation model test employed two regression equations, i.e., testing the relationship between earnings information and book value with stock prices and then testing the relationship between earnings information, book value, and cash flow with stock prices. In addition, the return model testing was performed to examine the relationship between earnings information and earnings changes with stock returns and the relationship between cash flow and cash flow changes with stock returns. The research sample was 105 manufacturing companies, with a research period from 2016 to 2019.Research findings: The test results with the pricing model approach revealed that earnings and cash flow had value relevance, while book value had no value relevance. This study’s results suggest that earnings and cash flow information are helpful for investors in making investment decisions. Moreover, the test results with the return model approach also uncovered those earnings, changes in earnings, and changes in operating cash flows had value relevance while operating cash flows, on the other hand, had no value relevance.Theoretical contribution/Originality: The utilized two models complement each other, and this study provides empirical evidence for standard setters who can renew beliefs about how much accounting information is reflected in stock prices in Indonesia, especially the manufacturing sector, after the full convergence of IFRS Financial Accounting Standards is applied.